The importance of additive technology and manufacturing processes for laboratory experiments in aeronautics - Tilvaldyev, Shehret A.; Caldiño Herrera, Uzziel; Dávalos Ramírez, José Omar; Lira Martinez, Manuel Alejandro; Muñoz Avitia, Edgar Alfonso (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2023)
In recent years, the world manufacturers of aviation equipment have made significant progress in the use of high efficiency (in terms of economic and time parameters) Additive Technology and Manufacturing processes. In aeronautics, at the stages of design, production and operation, laboratory tests and trials of various parts of the aircraft are very important and very often this can only be accomplished with the use of scaled-down prototypes.  Today, the best way to produce prototypes of various parts of the aircraft, is Additive Technology and Manufacturing processes. This article provides the reader with an opportunity to learn more about the use of additive manufacturing technologies for the needs of experimental activities in Aeronautics.